Maternal micronutrient deficiency and congenital heart disease risk: A systematic review of observational studies. Issue 17 (18th August 2022) - Mires, Stuart; Caputo, Massimo; Overton, Timothy; Skerritt, Clare
Abstract: Background: Congenital anomalies affect over 2% of pregnancies, with congenital heart disease (CHD) the most common. Understanding of causal factors is limited. Micronutrients are essential trace elements with key roles in growth and development. We aimed to investigate whether maternal micronutrient deficiencies increase the risk of fetal CHD through systematic review of published literature. Method: We performed a systematic review registered at PROSPERO as CRD42021276699. Ovid‐MEDLINE, Ovid‐EMBASE, and Cochrane Library were searched from their inception until September 7, 2021. Case control trials were included with a population of biological mothers of fetuses with and without CHD. The exposure was maternal micronutrient level measured in pregnancy or the postpartum period. Data extraction was performed by one author and checked by a second. Risk of bias assessment was performed according to the Scottish Intercollegiate Guidelines Network guidance. We performed a narrative synthesis for analysis. Results: 726 articles were identified of which 8 met our inclusion criteria. Final analysis incorporated data from 2, 427 pregnancies, 1, 199 of which were complicated by fetal CHD assessing 8 maternal micronutrients: vitamin D, vitamin B12, folate, vitamin A, zinc, copper, selenium, and ferritin. Studies were heterogenous with limited sample sizes and differing methods and timing of maternal micronutrient sampling. Definitions of deficiency varied and differed from published literature. Published results were contradictory. Conclusion: There is not enough evidence to confidently conclude if maternal micronutrient deficiencies increase the risk of fetal CHD. Further large‐scale prospective study is required to answer this question.